Complex N-Glycans Are Important for Normal Fruit Ripening and Seed Development in Tomato - Kaulfürst-Soboll, Heidi; Mertens-Beer, Melanie; Brehler, Randolf; Albert, Markus; von Schaewen, Antje (Frontiers in Plant Science, 2021)
Complex N-glycan modification of secretory glycoproteins in plants is still not well understood. Essential in animals, where a lack of complex N-glycans is embryo-lethal, their presence in plants seemed less relevant for a long time mostly because Arabidopsis thaliana cgl1 mutants lacking N-acetyl-glucosaminyltransferase I (GNTI, the enzyme initiating complex N-glycan maturation in the Golgi apparatus) are viable and showed only minor impairments regarding stress tolerance or development. A different picture emerged when a rice (Oryza sativa) gntI T-DNA mutant was found to be unable to reach the reproductive stage. Here, we report on tomato (Solanum lycopersicum) lines that showed severe impairments upon two RNA interference (RNAi) approaches. Originally created to shed light on the role of core α1,3-fucose and β1,2-xylose residues in food allergy, plants with strongly reduced GNTI activity developed necrotic fruit-attached stalks and early fruit drop combined with patchy incomplete ripening. Correspondingly, semiquantitative RT-PCR of the abscission zone (az) revealed an increase of abscission markers. Also, GNTI-RNA interference (RNAi) plants were more susceptible to sporadic infection. To obtain vital tomatoes with comparable low allergenic potential, Golgi α-mannosidase II (MANII) was chosen as the second target. The resulting phenotypes were oppositional: MANII-reduced plants carried normal-looking fruits that remained attached for extended time without signs of necrosis. Fruits contained no or only few, but enlarged, seeds. Furthermore, leaves developed rolled-up rims simultaneously during the reproductive stage. Trials to cross MANII-reduced plants failed, while GNTI-reduced plants could be (back-)crossed, retaining their characteristic phenotype. This phenotype could not be overcome by ethephon or indole-3-acetic acid (IAA) application, but the latter was able to mimic patchy fruit ripening in wild-type. Phytohormones measured in leaves and 1-aminocyclopropane-1-carboxylic acid (ACC) contents in fruits showed no significant differences. Together, the findings hint at altered liberation/perception of protein-bound N-glycans, known to trigger auxin-like effects. Concomitantly, semiquantitative RT-PCR analysis revealed differences in auxin-responsive genes, indicating the importance of complex N-glycan modification for hormone signaling/crosstalk. Another possible role of altered glycoprotein life span seems subordinate, as concluded from transient expression of Arabidopsis KORRIGAN KOR1-GFP fusion proteins in RNAi plants of Nicotiana benthamiana. In summary, our analyses stress the importance of complex N-glycan maturation for normal plant responses, especially in fruit-bearing crops like tomato.